Transcriptome Analysis of Immune Response Against Edwardsiella tarda Infection in Spotted Sea Bass (Lateolabrax maculatus) - Zhaosheng Sun; Xia Li; Qingling Zhang; Wei Wang; Huan Wang; Tingshuang Pan; Qian Gao (Fishes)
Edwardsiella tarda is a gram-negative bacterium reported to be one of the most harmful pathogens in aquaculture. In this study, we conducted transcriptome profiling of the head kidney, liver, and spleen in spotted sea bass (Lateolabrax maculatus) infected with E. tarda. A total of 22,015 unigenes were detected by de novo assembly and annotated by comparison with the major databases (NR, GO, COG, KEGG, Swiss-Prot), with 21,065 (NR:95.68%), 11,320 (GO:51.42%), 20,464 (COG:92.95%), 21,295 (KEGG:96.73%), 18,791 (Swiss-Prot:82%). Subsequently, a substantial number of differentially expressed genes (DEGs) were identified (p-adjust < 0.05). In the head kidney, liver, and spleen, there were 1302 upregulated genes and 503 downregulated genes, 377 upregulated genes and 530 downregulated genes, and 1240 upregulated genes and 736 downregulated genes, respectively. Additionally, the expression levels of eight immune-related DEGs were validated by qRT-PCR, further verifying the reliability of the transcriptome data. To the best of our knowledge, this is the first analysis of the transcriptome profile of L. maculatus in response to E. tarda. These findings not only offer fundamental insights into the antibacterial immune mechanisms of spotted sea bass but also serve as a reference for formulating more effective fish disease management strategies.